Presence at work: developing a nuanced understanding of worker presenteeism within context - Saade, Nathalie J. (2019)
The phenomenon of workplace ‘presenteeism’ is receiving scholarly attention across various disciplines and paradigms. The predominant conceptualization in organizational research refers to workers who are “attending work while ill” as opposed to being absent (Johns, 2010, p.521). Scholars are increasingly pointing to presenteeism as a key contemporary concern at work. One important argument is that further to developments in political economy and employment relations, workers are becoming “too scared to go sick” (Taylor et al., 2010, p.270). Presenteeism has been defined variably throughout the literature. This doctoral thesis traces conceptualizations of presenteeism across disciplines and argues for the value of considering nuances in workers’ experiences towards theoretical development of the construct.